DECREASING ELECTRICAL ENERGY COST AND INDIRECT CO2 EMISSIONS OF AN AIR CONDITIONING UNIT AFTER PREVENTIVE MAINTENANCE - Risonarta, Victor Yuardi; Widodo, Agung Sugeng (International Journal of Mechanical Engineering Technologies and Applications, 2024)
During the summer season in subtropical countries and the dry season in tropical countries, air temperature is high. To adapt this condition, an air conditioning (AC) unit is used. The air conditioning use, however, increases the electrical energy consumption which contributes to the increase of indirect CO2 emissions. For many buildings, a monthly electrical energy cost from the use of AC system can contribute up to 40% of a monthly utility expenditure. It is then a great motivation to decrease electrical energy consumption of the AC unit. In this work, an adaptable preventive maintenance for an AC unit shows an acceptable level of electrical energy decrease. An experiment was performed for 2 AC types. The first one is a wall mounted unit with a cooling capacity of 9,300 BTUH.  The second unit is a split duct unit with a cooling capacity of 48,000 BTUH. The cleaning of evaporator in the wall-mounted AC unit decreased the hourly electrical energy consumption by 4.1% from 810 to 777 Watt-hour. In addition, cleaning of condenser for the similar AC unit decreased the electrical energy consumption by 6.2% from 810 to 760 Watt-hour. Meanwhile, the evaporator cleaning for a 48,000 split duct AC decreased the hourly electrical energy consumption by 2.4% from 4.64 to 4.53 kWh and cleaning of condenser decreased the energy consumption by 5.4% from 4.64 to 4.39 kWh. If this electrical energy decrease could be scaled up to the global energy consumption from the air conditioning use, this should be a significant decrease of the global energy consumption and the correlated indirect CO2 emissions from the air conditioning sector.